Exploring Hospital Supply Chain Partnership Factors and Its Impact on Overall Supply Chain Performance - Marla Setiawati; Aiko Pasaribu; David Prasetya Halim; Juan Darmawan (Master of Management, School of Business and Management, Petra Christian University, 2023)
Hospitals function as complex businesses with intricate supply chain networks involving collaboration among various entities to efficiently deliver information, goods, and services to end customers. This study investigates the causal relationships between hospitals, suppliers, and government entities within the supply chain network. Employing system thinking, system dynamics, and causal-loop diagrams, it assesses how coordination, collaboration, and integration impact hospital supply chain performance. The findings reveal that high coordination and collaboration among suppliers, hospitals, and government entities positively influences supply chain performance. The study identifies key factors contributing to effective partnerships, such as information sharing, trust levels, supplier quality standards, inventory capabilities, flexibility, pricing strategies, and IT integration. Additionally, the research considers hospitals' dynamic capabilities, key performance results, patient outcomes, government healthcare spending, regulations, and economic indicators. Managerial implications emphasize the importance of strong partnerships to enhance overall supply chain performance, potentially improving patient outcomes and healthcare service quality. While acknowledging limitations, the study suggests future research avenues, including exploring the impact of other stakeholders and specific factors on hospital supply chain management.